Two new species of Willowsia (Collembola: Entomobryidae) from Guizhou Province, China - Ma, Yitong (Zootaxa, 2016)
The genus Willowsia Shoebotham, 1917 belongs to the family Entomobryidae. Within the family it is characterised by having 4-segmented antennae, 8+8 eyes, spines and scales absent from dens, claw with unpaired inner teeth, bidentate mucro and scales on body. Twenty-six species have been described in the genus worldwide including eight species from China. Two new species, Willowsia pseudoshi sp. nov. and W. variabilis sp. nov., from China are described here. The former species has pale yellow antennae except for distal part of Antenna IV which has some blue pigment and 4 macrochaetae are present on Abdomen I. The latter species has the whole antenna pigmented blue and 7−8 macrochaetae present on Abdomen I. A key to Chinese species of Willowsia is given.